Deep knowledge of B2B relationships within and across borders - Woodside, Arch G.; Baxter, Roger, 1944- (Advances in business marketing & purchasing ;, 2013)
Relationships of individual and groups among three-plus firms represent the cornerstone concept in business-to-business (B2B) contexts. The three-plus firms include manufacturer-supplier to manufacturer-customer to distributor-customer, and facilitators (e.g., transportation and management consulting firms). The common thread of the five papers in this volume is that making sense and achieving deep knowledge of three-plus B2B relationships are necessary antecedents for achieving high operating effectiveness, high (on-time) efficiency, and sustaining profits for each firm in these relationships. As the titles of the five papers imply, reading the volume provides deep insights into the specifics of how high performing three-plus B2B relationships influences these three major objectives of the firm : National cultures? Impacts on Western industrial buyer-seller relational process models; Developing Guanxi relations; Industrial buyer-seller relations in a Chinese context; Adaptation in business contexts; Working triadic relationships; How do managers see it? Capturing practitioner theories via network pictures.